1997
DOI: 10.1099/0022-1317-78-11-3061
|View full text |Cite
|
Sign up to set email alerts
|

A polydnavirus-encoded protein of an endoparasitoid wasp is an immune suppressor.

Abstract: The molecular mechanism by which polydnaviruses of endoparasitoid wasps disrupt cell-mediated encapsulation reactions of host insects is largely unknown. Here we show that a polydnavirus-encoded protein, produced from baculovirus and plasmid expression vectors, prevents cell surface exposure of lectin-binding sites and microparticle formation during immune stimulation of haemocytes. The inactivation of immune-related cellular processes by this protein was analysed using a specific lectin and annexin V and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 32 publications
3
64
0
1
Order By: Relevance
“…[9][10][11]. These viruses deliver genes into host caterpillars that, when expressed, produce proteins implicated in immune and developmental alterations in the caterpillar (12)(13)(14)(15)(16). In addition, they also may wield proteins on their capsid surface that disguise the parasitoid egg as it enters the caterpillar's hemocoel (17).…”
mentioning
confidence: 99%
“…[9][10][11]. These viruses deliver genes into host caterpillars that, when expressed, produce proteins implicated in immune and developmental alterations in the caterpillar (12)(13)(14)(15)(16). In addition, they also may wield proteins on their capsid surface that disguise the parasitoid egg as it enters the caterpillar's hemocoel (17).…”
mentioning
confidence: 99%
“…Hemocyte Changes after CrBV Incubation with or without Vn1.5-We have shown previously that CrBVs do not cause cell death in host hemocytes (12,26). The main effect observed in hemocytes after parasitization and infection by CrBVs was a breakdown of cell cytoskeleton, which precluded the spreading and encapsulation responses.…”
Section: Venom Is Required For Crbv Gene Expression-tomentioning
confidence: 94%
“…They are abundantly expressed in various host tissues, providing active protection by suppressing host cellular responses (26,27). A 32-kDa protein associated with particles is produced in calyx cells and covers the eggs of the parasitoid, providing passive immune protection while CrBV genes are expressed (28,29).…”
mentioning
confidence: 99%
“…Whereas high levels of transcripts were observed in haemocytes of the host caterpillar Pieris rapae within 4 h p.p., no transcripts were detectable at 12 h p.p. (Asgari et al, 1996(Asgari et al, , 1997. When the promoter region of the CrV1 gene was cloned into the baculovirus expression system with the CAT reporter gene, the CrV1 promoter was active as early as 2 h p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, EP1 transcripts could be detected in vitro after 6 days, which is more than half the time needed for larval development . In contrast, the expression of the Cotesia rubecula bracovirus (CrBV) gene, CrV1, is unique in that its expression is highly transient, occurring 4-8 h p.p., after which transcript abundance dramatically declines (Asgari et al, 1996(Asgari et al, , 1997. Promoter studies of the CrV1 gene suggested that upregulation is achieved by the promoter and upstream regulatory elements, whereas downregulation has been proposed to be due to posttranscriptional effects in CrV1-producing cells (Asgari & Schmidt, 2001).…”
Section: Introductionmentioning
confidence: 99%